The Effect of Rehabilitation Program on Improving Skeletal Divergence According to Designed Program for Women after Birth - Ibraheem, Mariam Ahmed; Rasheed, Wassan Saeed (Journal of Physical Education, 2021)
The problem of the research lies in women after pregnancy suffering from skeletal divergence due to long periods of pregnancy accompanied by weight gain, lack of movement, and mechanical variances. The researchers aimed at designing an apparatus for identifying skeletal divergence in women after birth as well as designing a rehabilitation program for correcting this divergence. The researchers applied the research on (7) women aged (24 – 32) years old who gave birth 48 – 58 before starting this study and after the doctor’s consent. The results showed a great improvement in all variables under study.